DNA binding by the MATα2 transcription factor controls its access to alternative ubiquitin-modification pathways - Hickey, Christopher M. (Mol Biol Cell, 2018)
Like many transcription factors, the yeast protein MATalpha2 (α2) undergoes rapid proteolysis via the ubiquitin-proteasome system (UPS). At least two ubiquitylation pathways regulate α2 degradation: one pathway utilizes the ubiquitin ligase (E3) Doa10 and the other the heterodimeric E3 Slx5/Slx8. Doa10 is a transmembrane protein of the endoplasmic reticulum/inner nuclear membrane, whereas Slx5/Slx8 localizes to the nucleus and binds DNA nonspecifically. While a single protein can often be ubiquitylated by multiple pathways, the reasons for this “division of labor” are not well understood. Here we show that α2 mutants with impaired DNA binding become inaccessible to the Slx5/Slx8 pathway but are still rapidly degraded through efficient shunting to the Doa10 pathway. These results are consistent with the distinct localization of these E3s. We also characterized a novel class of DNA binding-defective α2 variants whose degradation is strongly impaired. Our genetic data suggest that this is due to a gain-of-function interaction that limits their access to Doa10. Together, these results suggest multiple ubiquitin-ligation mechanisms may have evolved to promote rapid destruction of a transcription factor that resides in distinct cellular subcompartments under different conditions. Moreover, gain-of-function mutations, which also occur with oncogenic forms of human transcription factors such as p53, may derail this fail-safe system.